Student Perception of Learning Models Basic Basic Technique Pencak Silat Based of Multimedia Interactive - Lestari, Hikmah; Lanos, Muhsana El Cintami (Universitas Negeri Semarang, 2020)
This study aims to determine students’ perceptions about the use of multimedia learning based on (1) students’ perceptions of students’ teaching styles, (2) the use of technology in learning, (3) the usefulness of technology in learning, (4) the need for multimedia development. This research is a descriptive quantitative research. The results of this study indicate that (1) students’ perceptions of learning styles obtained a value of 72.81%, with a good category (2) The use of interactive multimedia in learning 92.14%, very good (3) the usefulness of interactive multimedia in learning 89.64% very useful (4) The need for developing interactive multimedia is 92.50% with the category strongly agree. The results of this study indicate that the students’ perceptions of the development of the interactive multimedia-based single-handed single-handed learning model in the physical education study program at Pgri Palembang University are positive, for that it is necessary to develop a learning model for the basic techniques of interactive multimedia-based pencak silat